Effect of temperature and incident ion energy on nanostructure formation on silicon exposed to helium plasma. Issue 12 (6th September 2020) - Thompson, Matt; Shi, Quan; Kajita, Shin; Ohno, Noriyasu; Corr, Cormac
Abstract: Helium plasma can be used to deliver low‐energy (<100 eV) helium ions to stimulate the growth of nanostructures on silicon surfaces. This can produce a wide range of surface features including nanoscale roughening, nanowires and porous structures. In this study, nanostructure sizes varied from ∼10 to over 100 nm in diameter. The effect of these structures on surface reflectivity for photovoltaic and photocatalytic applications is also investigated. Broadband suppression of photoreflectivity is achieved across the 300–1, 200 nm wavelength range studied for silicon exposed to helium plasma at 600°C, with an average reflectivity of 3.2% and 2.9% for incident helium ion energies of 42 and 62 eV, respectively. Abstract : Silicon surfaces were modified by exposure to low energy helium ions via helium plasma. Nanowires, networked structures and surface roughening could all be achieved by altering the substrate temperature and incident ion energies. Nanowire structures demonstrated excellent broad‐band anti‐reflection properties, with reflectivity values averaging only 2.9% over the 300 nm to 1200 nm wavelength range studied for silicon exposed to 62 eV helium ions at a substrate temperature of 600C.